Thermally conductive h-BN reinforced PEI composites: The role of processing conditions on dispersion states - Bozkurt, Yunus Emre; Yıldız, Alptekin; Türkarslan, Özlem; Şaşal, Feride N.; Cebeci, Hulya (Elsevier BV, 2021)
Abstract In this study, h-BN, reinforced PEI composites were studied up to 30 wt% through optimizing process conditions of melt-mixing to tune the thermal conductivity at relatively low-filler ratios while possessing a scalable manufacturing process with thermoplastics operating at high temperatures. The effects of processing parameters on the rheological properties and thermal conductivities of resulting h-BN/PEI composites were determined. DSC and TGA analyses showed that h-BN addition did not lead to a significant change in Tg; however, thermal decomposition temperatures of PEI were shifted. At 30 wt% h-BN loading, a high thermal conductivity as 0.82 W/mK was achieved, which is three times that of neat PEI. The significant enhancement in thermal conductivity was attributed to effective dispersion state of h-BN, creating an enhanced phonon transport mechanism confirmed through rheological analysis. This work provides a thermo-economic solution with relatively low-filler loading ratios in a high temperature and high performance operating polymer. These polymer composites were successfully fabricated in a filament form as candidates for lightweight advanced packaging materials by either injection molding or 3D printing.